Trust-building in the mentoring of students of color. Issue 1 (1st January 2018) - Chan, Anne
Abstract: Trust is a vital component of mentoring, particularly when protégés are people of color who have experienced racism and discrimination. My findings are part of a larger study that culminated in the formulation of a theory of multicultural mentoring. Trust was found to be foundational for successful multicultural mentoring relationships. In my study of how mentors establish trust with graduate protégés of color, the following mentor practices were found to promote trust: listening, maintaining excellent communication, having a holistic understanding of the protégé, self-disclosing, using humor, being willing to discuss race and culture, acknowledging mistakes, and behaving with integrity. The mentors not only worked to establish interpersonal trust, they also attended to institutional and sociocultural trust concerns that impacted their protégés. Considerable time, skill, commitment, and effort are required for mentors to establish trust with protégés of color. Recommendations for the provision of mentor support are provided.